Pentingnya Evaluasi Pendidikan Islam Dalam Proses Pembelajaran - Hannisa Mustika (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2019)
This study discusses important of evaluation of education in learning. In the world of Islamic education, all teaching and learning activities are carried out well to achieve an educational goal. In Islamic education, the main goal to be achieved is to increase the faith and piety to Allah SWT. However, at this time a lot of Islamic schools that have not been able to achieve the goals of Islamic education. Many students who do not practice the knowledge obtained from school. For this reason, an education evaluation is needed so that educators and students can find out where their mistakes are. Educational evaluation aims to assess the extent to which learning is obtained by students. With this evaluation teachers and students are expected to be able to optimize the teaching and learning process in the classroom.